The association of dietary inflammatory potential with skeletal muscle strength, mass, and sarcopenia: a meta-analysis - Xie, Haibin; Wang, Haochen; Wu, Ziying; Li, Wei; Liu, Yanzhe; Wang, Ning (Frontiers in Nutrition, 2023)
Aims: Evidences suggested that dietary inflammatory potential may be associated with age-related skeletal muscle decline, but the results remained controversial. To summarize evidence for the relationships between dietary inflammatory potential and skeletal muscle strength, mass and sarcopenia in adults we conducted this meta-analysis. Methods: Embase, Pubmed and Web of science were searched from inception up to November 07 2022 for studies that evaluated the associations of dietary inflammatory potential (estimated by the Dietary inflammatory index [DII]) with skeletal muscle strength, mass, and sarcopenia. A meta-analysis was then performed to calculate the pooled regression coefficient (β) and odds ratio (OR). Results: This meta-analysis included 22 studies involving 50,735 participants. It was found that a high DII was associated with low skeletal muscle strength (OR 1.377, [95% CI 1.207, 1.570], P<0.001), but there was no significant association of DII with skeletal muscle strength (β 0, [95% CI -0.033, 0.010], P=0.301). Furthermore, a high DII was also associated with low skeletal muscle mass (OR 1.106 [95% CI 1.058, 1.157], P<0.001), while DII had a negative relationship with skeletal muscle mass (β -0.073, [95% CI -0.109, -0.038], P<0.001). Finally, the pooled results suggested that a high DII was significantly associated with sarcopenia (OR 1.443, [95% CI 1.202, 1.733], P<0.001). Conclusion: This meta-analysis suggested that higher dietary inflammatory potential was significantly associated with lower skeletal muscle strength, mass and higher prevalence of sarcopenia. Further studies are needed to confirm the causality.